Septic Arthritis associated with Actinomycosis in a Kid – A Case Report - Karthika, K. (The Indian Veterinary Journal, 2026)
A one-month-old kid was presented with the history of lameness, swelling in all the joints and complete anorexia for the past 3 days. The clinical examination revealed an enlarged lymph node, an elevated rectal temperature (39.6 °C), and soft swelling in the joints of all limbs. Based on the history and clinical findings, the case was diagnosed as Septic arthritis associated with actinomycosis. The treatment was done with anti-microbial therapy, Amikacin @15mg/kg, NSAID Meloxicam @0.5mg/kg, with supportive care. The animal showed complete recovery after 10 days of treatment.